Dismal prognosis of patients with operative indication without surgical intervention in active left-sided infective endocarditis - Van Hemelrijck, Mathias; Sromicki, Juri; Frank, Michelle; Greutmann, Matthias; Ledergerber, Bruno; Epprecht, Jana; Padrutt, Maria; Vogt, Paul R.; Carrel, Thierry P.; Dzemali, Omer; Mestres, Carlos-A.; Hasse, Barbara (Frontiers in Cardiovascular Medicine, 2023)
Introduction: Around 25% of patients with left-sided infective endocarditis and operative indication do not undergo surgery. Baseline characteristics and outcomes are underreported. This study describes characteristics and outcomes of surgical candidates with surgical intervention or medical treatment only. Methods Retrospective analysis of ongoing collected data from a single-center from an observational cohort of patients with infective endocarditis (ENVALVE). Kaplan-Meier estimates for survival was calculated. Factors associated with survival were assessed using a bivariable Cox model. To adjust for confounding by indication, uni- and multivariable logistic regression for the propensity to receive surgery were adjusted. Results: From January 2018 and December 2021, 154 patients were analyzed: 116 underwent surgery and 38 received medical treatment only. Surgical candidates without surgery were older (70 vs 62 years, p=0.001). They had higher preoperative risk profile (EuroSCORE II 14% (7.2-28.6) vs 5.8% (2.5-20.3), p=0.002) and more comorbidities. One patient was lost-to-follow-up. Survival analysis revealed a significant higher one-year survival rate among patients following surgery (83.7% vs 15.3% in the non-surgical group; log-rank test <0.0001). In the final multivariable adjusted model, surgery was less likely among patients with liver cirrhosis (OR =0.03 [95% CI 0.00-0.30]) and with hemodialysis (OR =0.014 [95% CI 0.00-0.47]). Conclusion. Patients with left-sided infective endocarditis who do not undergo surgery despite an operative indication are older, have more comorbidities and therefore higher preoperative risk profile and a low 1-year survival. The role of the Endocarditis Team may be particularly important for the decision-making process in this specific group.